Non-Military Preventive Efforts In Handling Human Rights Violations Against Armed Violent Groups in Papua, Indonesia - Mardiana; Rahmadina, Adji Annisa; Bone, Sholihin (PT. Anagata Sembagi Education, 2024)
This research explores the non-military preventive approach as a solution to human rights violations committed by the Armed Violence Group (KKB) in Papua. Using normative juridical methods, this research examines human rights law regulations in Indonesia, literature studies, and analysis of Gus Dur's speeches and writings on the peaceful approach. The conflict in Papua, fueled by a history of discrimination, exploitation of natural resources, and centralized policies, has been exacerbated by an often ineffective military approach. Comprehensive solutions are needed to address the injustice, poverty and human rights violations experienced by Papuans. This research proposes a strategy based on inclusive dialog, local participation, and respect for Papuan identity. This approach is rooted in the principles of justice, equality and human values upheld by Gus Dur. In addition, efforts to empower the economy, education, and infrastructure development in favor of indigenous peoples are considered important for creating sustainable peace. The results show that conflict resolution in Papua requires not only security solutions, but also strategic steps that prioritize social welfare and human rights protection, thus strengthening national cohesion within the framework of the Unitary State of the Republic of Indonesia (NKRI).